Does Financial Literacy Contribute to the Increased Utilization of Digital Transactions by MSMEs? - Agus Wahyudi Salasa Gama; Gregorius Paulus Tahu; I Nengah Suardhika; Putu Intan Liliana Putri; Desak Nyoman Sri Pratiwi; Ni Made Putri Dwita Utami (Philippine Social Science Journal, 2025)
To understand the role of financial knowledge in the digital economy, this study examined the influence of financial literacy on digital transaction usage among 100 MSMEs in Bali. Utilizing the Mann-Whitney U test, the analysis revealed that entrepreneurs with high financial literacy utilize digital transactions significantly more than those with lower literacy levels, largely due to a better grasp of the associated benefits and risks. These findings underscore the practical necessity of enhancing financial literacy to improve MSME competitiveness and operational efficiency. Consequently, future research should employ larger, geographically diverse samples and advanced statistical methods to further explore causal relationships and other variables influencing technology adoption.